Strong polymer molecular weight-dependent material interactions: impact on the formation of the polymer/fullerene bulk heterojunction morphology. Issue 25 (14th June 2017) - Kim, Joo-Hyun; Gadisa, Abay; Schaefer, Charley; Yao, Huifeng; Gautam, Bhoj R.; Balar, Nrup; Ghasemi, Masoud; Constantinou, Iordania; So, Franky; O'Connor, Brendan T.; Gundogdu, Kenan; Hou, Jianhui; et al.
Abstract : The morphological evolution is initiated by L–L or L–S phase separation (left) and further developed by molecular mobility, governed by polymer–solvent interactions which determine the final domain size of the BHJ layer (right). Abstract : The performance of polymer–fullerene bulk heterojunction (BHJ) solar cells is highly affected by the morphology of the blend film. Though the structure of the BHJ morphology is well-understood, the relationship between relevant material interactions and BHJ morphological evolutions is poorly understood and seldom explored. In this report, we discuss the impact of polymer molecular weight (MW) on thermodynamic and kinetic phenomena which have a drastic influence on the nanoscale BHJ morphology. The blend film comprises a highly aggregating low bandgap diketopyrrolopyrrole-based polymer PDPP3T and the fullerene electron acceptor molecule PC71 BM, cast from a 1, 2-dichlorobenzene (DCB) solution with and without the additive 1, 8-diiodooctane (DIO). The pair-wise interactions among the components were evaluated by Flory–Huggins interaction parameters ( χ ). The BHJ blend of PDPP3T and PC71 BM exhibited liquid–liquid (L–L) phase separation as a result of strong polymer–fullerene interactions (large χ PDPP3T–fullerene ) in DCB solution. In contrast, addition of 3% DIO into the DCB solution is found to stimulate polymer aggregation which gives rise to liquid–solid (L–S) phase separation. Large χ PDPP3T–fullerene and χ PDPP3T–solvent were observed as a result of increasing polymer MW, and these changes promote strong L–L phase separation and polymer aggregation in the blend solution, respectively. The latter interactions have led to low molecular mobility, with an end result of reduced crystallinity and smaller domain size of the BHJ films. The observed dramatic MW-dependent morphological changes were also manifested in solar cell outputs as well as charge carrier dynamics calculated by transient absorption measurements.